The photojournalistic work of Tino Calabuig and the exhibition Cinco años de fotografía de prensa (Galería Redor, 1980) as a collective visual memory of the Spanish Transition to democracy - Blázquez, Elena (Historia y Comunicación Social, 2025)
This study examines the photojournalistic work of visual artist Tino Calabuig during the Spanish transition to democracy. During this time he covered, among other events, the Vitoria and Atocha massacres, both in his photo reports and in films of the Colectivo de Cine de Madrid, a group he was a member of in the mid-1970s. The study also emphasizes Calabuig’s role as the director of the Galería Redor, where he organized the exhibition Cinco años de fotografía de prensa in 1980. This article underscores the importance of this exhibition, not only as a key showcase of the most significant events of the transition to democracy, but also as a pioneering initiative that sought to affirm the informative and historical-cultural value of photojournalism.